Jerry’s cost is $.04 per message
It is 4/3. the quantity of 4 over 3
X+6/3 - x+2/3= x+6-x-2/3 = 4/3.
Answer:
(-19 , -7)
Step-by-step explanation:
y - x = 12
y + x = -25 we sum them to get
2y = -14 , y = -7
then we put -7 instead of y in any of the equations:
-7 - x = 12
-x = 19
x = -19,
finally (x , y) is (-19 , -7)
Answer:
x = 17, MN = 11
Step-by-step explanation:
Given 2 secants from an external point to a circle, then
The product of the external part and the whole of one secant is equal to the product of the external part and the whole of the other secant.
(5)
7(7 + x) = 8(8 + 13) = 8 × 21 = 168 ( divide both sides by 7 )
7 + x = 24 ( subtract 7 from both sides )
x = 17
(6)
9(9 + 2x - 7) = 10(10 + 8)
9(2x + 2) = 10 × 18 = 180 ( divide both sides by 9 )
2x + 2 = 20 ( subtract 2 from both sides )
2x = 18 ( divide both sides by 2 )
x = 9
Then
MN = 2x - 7 = 2(9) - 7 = 18 - 7 = 11
Answer:
f = -3/4
Step-by-step explanation:
13f + 6 -f = -3
Combine like terms
12f +6 = -3
Subtract 6 from each side
12f+6-6 = -3-6
12f = -9
Divide each side by 12
12f/12 = -9/12
f = -3/4